The role of FOXP3 in autoimmunity. (December 2016) - Pesenacker, Anne M; Cook, Laura; Levings, Megan K
Highlights: Dysregulation of FOXP3 expression can occur at multiple levels in autoimmunity. Autoimmune SNPs diminish IL-2 sensitivity and FOXP3, resulting in impaired Tregs. Splicing, post-translational modification, and subcellular localization regulate FOXP3. Many new Treg-targeted therapies are being tested in autoimmunity. Abstract : FOXP3 controls the development and function of T regulatory cells (Tregs). Autoimmunity is linked to changes in FOXP3 activity that can occur at multiple levels and lead to Treg dysfunction. For example, changes in IL-2 signaling, FOXP3 transcription and/or post-translational modifications can all contribute to loss of self-tolerance. As additional pathways of FOXP3 regulation are elucidated, new therapeutic approaches to increase Treg activity either by cell therapy or pharmacological intervention are being tested. Early success from pioneering studies of Treg-based therapy in transplantation has promoted the undertaking of similar studies in autoimmunity, with emerging evidence for the effectiveness of these approaches, particularly in the context of type 1 diabetes.